DYRK1A (Dual-Specificity Tyrosine-Phosphorylated and -Regulated Kinase 1A): A Gene with Dosage Effect During Development and Neurogenesis - M. Dierssen; M. Martínez de Lagrán (The Scientific World Journal)
DYRKs (dual-specificity tyrosine-regulated kinases) are an emerging family of evolutionarily conserved dual-specificity kinases that play key roles in cell proliferation, survival, and development. The research in the last years suggests a relevant conserved function during neuronal development, related to proliferation and/or differentiation for DYRK1A. It is expressed in neural progenitor cells and has been proposed to participate in the signaling mechanisms that regulate dendrite differentiation. In Drosophila, disruption of the homolog minibrain gene results in flies with reduced neuroblast proliferation, decreased numbers of central brain neurons, and learning/memory deficits. Knockout DYRK1A mice are embryonic lethal, and heterozygotes show decreased viability and region-specific reductions in brain size. In humans, DYRK1A has been proposed to be involved in the neurodevelopmental alterations associated with Down syndrome. The large number of protein interaction and putative substrates described for DYRK1A suggest multiple pathways and functions to be involved in its developmental function. This review focuses on the functional role that DYRK1A plays in brain development.